MODEL PENGEMBANGAN PRODUK HALAL - Najiatun; Ryan Rahmah Maulayati (Jurnal Investasi Islam, 2019)
The purpose of this study is to develop food products that can be seen from the components of the food product system, namely production and distribution. The results of the research in developing a halal product it is necessary to do 3 things, namely: First, halal logistics to ensure halal products are not contaminated by non-halal products during the distribution process by the manufacturer. Second, halal certiﬁ cation is the process of certiﬁ cation of products or services in accordance with the provisions of Islamic sharia and avoid being prohibited by Allah. Third, halal veriﬁ cation is to educate consumers about the importance of consuming halal products.